2012
DOI: 10.4236/health.2012.410127
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ willingness to work in post-conflict areas: A qualitative study in Sri Lanka

Abstract: Background: The north-east (NE) region of Sri Lanka observed a critical health workers' shortage after the long-lasting armed conflict. This study aimed to explore medical students' attitudes towards working in the NE and to identify factors determining such attitudes. Methods: A semi-structured, self-administered questionnaire survey was conducted in two medical schools, one in the NE and the other near the capital, in October 2004. Data were qualitatively analysed using the framework approach. Results: Three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…The earlier few studies have either considered a limited spectrum of items in the questionnaire or were conducted in developed nations. [ 4 , 12 , 16 , 17 , 35 , 36 ] After rigorous literature review and expert Delphi consultations, a questionnaire consisting of 33 items was developed which was named the MSDRI questionnaire. Interestingly, our analyses highlight 5 factors/subscales for the items listed in the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The earlier few studies have either considered a limited spectrum of items in the questionnaire or were conducted in developed nations. [ 4 , 12 , 16 , 17 , 35 , 36 ] After rigorous literature review and expert Delphi consultations, a questionnaire consisting of 33 items was developed which was named the MSDRI questionnaire. Interestingly, our analyses highlight 5 factors/subscales for the items listed in the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…Gadi, [ 4 ] Kotzee and Couper, [ 5 ] Manongi et al, [ 6 ] Shankar and Thapa, [ 12 ] Henderson and Tulloch, [ 37 ] Lori et al, [ 35 ] Kaye et al, [ 38 ] and Steinhaeuser et al [ 39 ] have mentioned items related to professional challenge as the barriers for medical students to serve in rural areas. Few studies in the context of the social segregation subscale are Gadi, [ 4 ] Saini et al, [ 16 ] Sinha, [ 17 ] Shankar and Thapa, [ 12 ] Lori et al, [ 35 ] and Kaye et al [ 38 ] who concluded that low standard of living impedes medical students for working in rural areas. A study by Henderson and Tulloch [ 37 ] has reported that items related to hostile professional environment were responsible barriers for health workers for accepting rural postings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations